Non associated-anisotropic plasticity model fully coupled with isotropic ductile damage for sheet metal forming applications. (July 2019) - Ghorbel, O.; Koubaa, S.; Mars, J.; Wali, M.; Dammak, F.
Abstract: This paper presents an implementation of a fully coupled non-associated anisotropic plasticity-ductile damage model, including a mixed nonlinear isotropic- kinematic hardening. With the non-associated anisotropic plasticity assumption, the yielding and plastic potential are determined independently. The quadratic Hill'48 function is considered for yield and plastic potential to describe the anisotropic plastic behavior of DD13 sheets. A three non-linear local scalar equation problem is solved using the Newton–Raphson method. The numerical resolution of the proposed algorithm is implemented into ABAQUS using the user interface material subroutines (UMAT and VUMAT). A consistent tangent operator is developed to preserve the quadratic rate of asymptotic convergence that characterizes Newton's method. The evaluation of the proposed implementation ability to predict the real behavior of DD13 steel material during forming is achieved using some experimental setups performed by the authors.